Multiple D2 heteroreceptor complexes: new targets for treatment of schizophrenia. (April 2016) - Borroto-Escuela, Dasiel O.; Pintsuk, Julia; Schäfer, Thorsten; Friedland, Kristina; Ferraro, Luca; Tanganelli, Sergio; Liu, Fang; Fuxe, Kjell
The dopamine (DA) neuron system most relevant for schizophrenia is the meso-limbic-cortical DA system inter alia densely innervating subcortical limbic regions. The field of dopamine D2 receptors and schizophrenia changed markedly with the discovery of many types of D2 heteroreceptor complexes in subcortical limbic areas as well as the dorsal striatum. The results indicate that the D2 is a hub receptor which interacts not only with many other G protein-coupled receptors (GPCRs) including DA isoreceptors but also with ion-channel receptors, receptor tyrosine kinases, scaffolding proteins and DA transporters. Disturbances in several of these D2 heteroreceptor complexes may contribute to the development of schizophrenia through changes in the balance of diverse D2 homo- and heteroreceptor complexes mediating the DA signal, especially to the ventral striato-pallidal γ-aminobutyric acid (GABA) pathway. This will have consequences for the control of this pathway of the glutamate drive to the prefrontal cortex via the mediodorsal thalamic nucleus which can contribute to psychotic processes. Agonist activation of the A2A protomer in the A2A–D2 heteroreceptor complex inhibits D2 Gi/o mediated signaling but increases the D2 β-arrestin2 mediated signaling. Through this allosteric receptor–receptor interaction, the A2A agonist becomes a biased inhibitory modulator of the Gi/o mediated D2 signaling, which may the main mechanism for its atypical antipsychotic properties especially linked to the limbic A2A–D2 heterocomplexes. The DA and glutamate hypotheses of schizophrenia come together in the signal integration in D2– N -methyl-d -aspartate (NMDA) and A2A–D2–metabotropic glutamate receptor 5 (mGlu5) heteroreceptor complexes, especially in the ventral striatum. 5-Hydroxytryptamine 2A (5-HT2A)–D2 heteroreceptor complexes are special targets for atypical antipsychotics with high potency to block their 5-HT2A protomer signaling in view of the potential development of pathological allosteric facilitatory 5-HT2A–D2 interaction increasing D2 protomer signaling. Neurotensin (NTS1)–D2 heterocomplexes also exist in the ventral and dorsal striatum, and likely also in midbrain DA nerve cells as NTS1-D2 autoreceptor complexes where neurotensin produces antipsychotic and propsychotic actions, respectively.